Age-related changes in implicit emotion processing. Issue 1 (2nd January 2019) - Manenti, Rosa; Brambilla, Michela; Cotelli, Maria
ABSTRACT: The aim of the present study was to compare the performance of older and younger adults on an emotional priming task. Moreover, a nonemotional priming paradigm was used as a control task to disentangle age-related changes due to emotional processing difficulties from modifications due to a decline of executive inhibitory control abilities. Twenty-two young and 22 older healthy participants completed an emotional priming task and a nonemotional priming task. In the older adult group, reaction times in the emotional priming paradigm were not influenced by any of the prime conditions, whereas both groups exhibited similar facilitation effects induced by the congruent prime in the nonemotional task. The selective lack of an emotional priming effect in older adults shown in this preliminary report suggests that aging-induced changes in the ability to recognize emotions implicitly are directly dependent on emotional processing difficulties and not due to a general age-related modification of cognitive processes.